Pembelajaran Filsafat di Perguruan Tinggi Islam: Telaah Metode dan Penilaian Mahasiswa di STAI Darussalam - Irfan Putra Ramadhan; Ayu Maryani; Syalwa Nurdzakia; Wahyuni Hidayat; Ilmi Siti Najmah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article aims to describe the teaching methods and practices of the Philosophy of Islamic Education course at STAI Darussalam. This research uses a qualitative descriptive approach with a field study method that focuses on the learning process, the competencies to be achieved, teaching methods, assignment formats, evaluation systems, and obstacles encountered during the course. Data were obtained through observation and information gathering related to the implementation of the Philosophy of Islamic Education course. The results show that the teaching of the Philosophy of Islamic Education at STAI Darussalam focuses on understanding the nature of Islamic education, developing students' critical thinking patterns, improving educational literacy, and linking philosophical studies to social and political realities. The lecture method remains the dominant method used by lecturers, with an emphasis on students' ability to define and explain basic philosophical concepts accurately as an indicator of understanding. Learning success is measured by changes in students' thinking, which becomes increasingly critical, reflective, and contextual in responding to educational issues and social justice issues.